2016
DOI: 10.1080/15384101.2016.1186317
|View full text |Cite
|
Sign up to set email alerts
|

Negative control of CSL gene transcription by stress/DNA damage response and p53

Abstract: CSL is a key transcriptional repressor and mediator of Notch signaling. Despite wide interest in CSL, mechanisms responsible for its own regulation are little studied. CSL down-modulation in human dermal fibroblasts (HDFs) leads to conversion into cancer associated fibroblasts (CAF), promoting keratinocyte tumors. We show here that CSL transcript levels differ among HDF strains from different individuals, with negative correlation with genes involved in DNA damage/repair. CSL expression is negatively regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 56 publications
(72 reference statements)
1
18
0
Order By: Relevance
“…Atf3 up-regulation was transient and inversely related to Csl expression, which is down-modulated by UVA exposure of HDFs (Fig. S1 D; Menietti et al, 2016 ).…”
Section: Resultsmentioning
confidence: 97%
“…Atf3 up-regulation was transient and inversely related to Csl expression, which is down-modulated by UVA exposure of HDFs (Fig. S1 D; Menietti et al, 2016 ).…”
Section: Resultsmentioning
confidence: 97%
“…CSL can play biologically significant roles as a repressor of transcription independently of NOTCH activation (15). Control of CSL function in this context can occur through modulation of its expression (39,40). In human skin, immunofluorescence analysis showed that CSL is highly expressed in keratinocytes of lower epidermal layers, while it is substantially downmodulated in upper layers ( Figure 1A and Supplemental Figure 1A; supplemental material available online with this article; https://doi.org/10.1172/JCI96915DS1), in contrast with the opposite pattern of NOTCH 1/2 expression that we previously reported (41).…”
Section: Resultsmentioning
confidence: 99%
“…Concomitantly, we showed that CSL down-modulation increases HDF autophagy, mitophagy, and associated metabolic reprogramming ( Goruppi et al, 2017 ). Previous evidence reported that pro-carcinogenic stimuli such as ultraviolet A rays (UVAs) and smoke extract exposure, which induce autophagy ( Ratovitski, 2011 ; Sample et al, 2017 ), similarly down-regulate CSL ( Menietti et al, 2016 ). Using specific experimental conditions activating different types of autophagy, we determined that all inducers of autophagy affected CSL protein levels.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional control of autophagy is an area of active investigation ( Lapierre et al, 2015 ; Pietrocola et al, 2013 ) and autophagy and mitophagy have been implicated in CAF conversion ( Goruppi et al, 2017 ; Kalluri, 2016 ; Martinez-Outschoorn et al, 2017 ). Besides being negatively regulated by autophagy, down-modulation of CSL expression—as can result from exogenous pro-carcinogenic stimuli such as UV or smoke exposure ( Menietti et al, 2016 )—can by itself induce or reenforce the autophagic process ( Goruppi et al, 2017 ). An interesting possibility is that autophagy acts at multiple levels in CAF activation, initiating gene expression by increasing CSL turnover and by causing a cell-autonomous metabolic switch upon the increase of autophagy and mitophagy after CSL loss of function ( Goruppi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%